A perivascular niche in the bone marrow hosts quiescent and proliferating tumorigenic colorectal cancer cells. Issue 2 (4th March 2020) - Möhrmann, Lino; Zowada, Martina K.; Strakerjahn, Hendrik; Siegl, Christine; Kopp‐Schneider, Annette; Krunic, Damir; Strunk, Dirk; Schneider, Martin; Kriegsmann, Mark; Kriegsmann, Katharina; Herbst, Friederike; Ball, Claudia R.; et al.
Abstract : Disseminated tumor cells (dTCs) can frequently be detected in the bone marrow (BM) of colorectal cancer (CRC) patients, raising the possibility that the BM serves as a reservoir for metastatic tumor cells. Identification of dTCs in BM aspirates harbors the potential of assessing therapeutic outcome and directing therapy intensity with limited risk and effort. Still, the functional and prognostic relevance of dTCs is not fully established. We have previously shown that CRC cell clones can be traced to the BM of mice carrying patient‐derived xenografts. However, cellular interactions, proliferative state and tumorigenicity of dTCs remain largely unknown. Here, we applied a coculture system modeling the microvascular niche and used immunofluorescence imaging of the murine BM to show that primary CRC cells migrate toward endothelial tubes. dTCs in the BM were rare, but detectable in mice with xenografts from most patient samples (8/10) predominantly at perivascular sites. Comparable to primary tumors, a substantial fraction of proliferating dTCs was detected in the BM. However, most dTCs were found as isolated cells, indicating that dividing dTCs rather separate than aggregate to metastatic clones—a phenomenon frequently observed in the microvascular niche model. Clonal tracking identified subsets of self‐renewing tumor‐initiating cells in the BM that formed tumors out of BM transplants, including one subset that did not drive primary tumor growth. Our results indicate an important role of the perivascular BM niche for CRC cell dissemination and show that dTCs can be a potential source for tumor relapse and tumor heterogeneity. Abstract : What's new? Prior studies indicate that perivascular bone marrow niche can induce quiescence of disseminated tumor cells (dTCs), making bone marrow a suspected dTC reservoir. In this study, quiescent and proliferating colorectal cancer (CRC) cells were detected in the perivascular bone marrow niche of mice harboring patient‐derived xenografts. Xenotransplantation and clonal tracking of dTCs in the bone marrow revealed distinct tumor‐initiating cell subsets and demonstrated the ability of dTCs to serve as a cell source for tumor relapse and tumor heterogeneity. These functional data should prompt further studies to better define the prognostic value of dTCs in the clinical setting.